Model Jurnalisme Naratif dalam Novel Sang Pewarta - Annisa Nur Tiara; Alex Sobur (Bandung Conference Series: Journalism, 2022)
Abstract. Novel is a form of writing which is a mass media of journalistic products wrapped and packaged using literary language. This research on “The Model of Narrative Journalism in the Novel Sang Pewarta” aims to determine the structure of the 3-act narrative according to Tzevetan Todorov’s theory. To be later linked and distributed in scene o gram. Using qualitative research methods, with a narrative analysis approach and using the theory of narrative structure according to Tzevetan Todorov. Observation, Literature Study, and Document Study were conducted to collect data, and analyze it in 3 stages, namely data reduction, data presentation and then drawing conclusions. Finally, to test the validity of the data, it is done by triangulating the theory, linking the data with the existing theory. This study resulted in 3 research points, firstly that a narrative has an initial balancing act which is aimed at the initial 6 chapters of the novel describing the initial situation, secondly there are 17 chapters on conflict patterns where the main character is experiencing a lot of disturbances, the last there are 3 chapters in the novel. the final balance pattern, when the main character tries to restore balance. Abstrak. Novel, salah satu bentuk tulisan yang merupakan media massa produk jurnalistik yang dibalut dan dikemas menggunakan bahasa sastra. Penelitian tentang “Model Jurnalisme Naratif dalam novel Sang Pewarta” ini bertujuan untuk mengetahui struktur narasi 3 babak menurut teori Tzevetan Todorov. Menggunakan metode penelitian kualitatif, dengan pendekatan analisis naratif dan menggunakan teori struktur narasi menurut Tzevetan Todorov, untuk kemudian dikaitkan dan didistribusikan menggunakan scene o gram. Observasi, Studi Pustaka, dan Studi Dokumen dilakukan untuk mengumpulkan data, dan menganalisisnya dengan cara 3 tahap yaitu reduksi data, penyajian data kemudian penarikan kesimpulan. Terakhir, untuk menguji keabsahan data, dilakukan dengan triangulasi teori, mengaitkan data dengan teori yang ada. Penelitian ini menghasilkan 3 poin penelitian, pertama bahwa sebuah narasi memiliki babak keseimbangan awal yang ditujukan dengan 6 bab awal pada novel yang menggambarkan situasi awal, yang kedua terdapat 17 bab pada pola konflik dimana tokoh utama sedang mengalami banyak gangguan, yang terakhir terdapat 3 bab pada pola keseimbangan akhir, saat tokoh utama berusaha mengembalikan keseimbangan.